2002
DOI: 10.1046/j.1420-9101.2002.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Confidence of paternity and paternal care: covariation revealed through the experimental manipulation of the mating system in the beetle Onthophagus taurus

Abstract: Theoretical models of paternal care predict that facultative reductions in male care may occur under certain conditions. One important parameter that has been shown to influence the outcome of these models is a male's confidence of paternity. In this study, we tested whether the amount of care provided by horned males in the dimorphic beetle, Onthophagus taurus, varied with his confidence of paternity. Male care results in an increased weight of dung provided in the brood masses produced by the pair. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 91 publications
(207 reference statements)
2
53
1
Order By: Relevance
“…Recent studies indicate that male encounter rates and the intensity of male-male competition are directly proportional to the number of males present in a dung pad or experimental arena (Moczek, 1996;Hunt and Simmons, 2002). Furthermore, several studies have shown that dung removal rates increase with the number of conspecifics present in a given dung pad (Giller and Doube, 1989;Ridsdill-Smith et al, 1982) and that dung beetles, rather than other dung-associated insects, provide by far the greatest contribution to the removal of above-ground dung on Australian and eastern U.S. pastures (Bornemissza, 1970(Bornemissza, , 1976Hanski and Cambefort, 1991;Ridsdill-Smith, 1993).…”
Section: Generalmentioning
confidence: 99%
“…Recent studies indicate that male encounter rates and the intensity of male-male competition are directly proportional to the number of males present in a dung pad or experimental arena (Moczek, 1996;Hunt and Simmons, 2002). Furthermore, several studies have shown that dung removal rates increase with the number of conspecifics present in a given dung pad (Giller and Doube, 1989;Ridsdill-Smith et al, 1982) and that dung beetles, rather than other dung-associated insects, provide by far the greatest contribution to the removal of above-ground dung on Australian and eastern U.S. pastures (Bornemissza, 1970(Bornemissza, , 1976Hanski and Cambefort, 1991;Ridsdill-Smith, 1993).…”
Section: Generalmentioning
confidence: 99%
“…Minor males outnumber majors in the dung pad so that both morphs face a high risk of sperm competition. Indeed, the two morphs invest equally in ejaculates (Simmons et al 1999b), spend equivalent durations in copula and gain fertilizations in direct proportion to the relative number of copulations they perform with a female (Tomkins & Simmons 2000;Hunt & Simmons 2002). The average pattern of sperm use strongly suggests that sperm mix randomly in the female's genital tract.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to males, female fitness components (i.e. fecundity and survival) increase linearly across the natural range of female body sizes when females provision in isolation (Hunt and Simmons 2002). We do not currently know, however, whether the increase in fitness with size is greater in males or in females when measured under the same conditions, but we suspect the latter is more likely due to intense sperm competition in this species (Simmons et al 1999).…”
Section: Dung Beetle Life-historymentioning
confidence: 87%